PENGAWASAN DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA (DISHUBKOMINFO) KOTA PEKANBARU TERHADAP FUNGSI TERMINAL ANGKUTAN UMUM BANDAR RAYA PAYUNG SEKAKI KOTA PEKANBARU TAHUN 2016 - Muhammad Rangga Sudrajat; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Terminal Bandar Raya Payung Sekaki serve as the infrastructure for road transport for the purposes of loading and lowering people's arrival and departure as well as organizing public transport. But in fact many of the transporter driver does not utilize the terminal, they prefer to raise and lower the passengers outside the terminal. This often happens because the lack of surveillance conducted by the Department of transport communications and Informatics Pekanbaru so that terminal does not run in accordance with the functions originally. Based on these phenomena, the formulation of the problem in this research is how the supervision of the Department of transport communications and Informatics Pekanbaru against public transport terminal function Bandar Raya Payung Sekaki Pekanbaru in 2016 and what are the factors restricting in the surveillance.The purpose of this research is to know the supervision Department of transport communications and Informatics Pekanbaru against public transport terminal function Bandar Raya Payung Sekaki Pekanbaru in 2016 and restricting factors in the surveillance. The concept of the theory that researchers use the supervisory process is according to the Simbolon’s theory, the indicators in this study is, the plan must be determined, the injunction against the implementation of the work, purposes, and predetermined policies. This research uses qualitative descriptive method approach. In data collection, researchers use interview techniques, observation and documentation.The results of the research Department of transportation oversight is the author of the communication and Informatics Pekanbaru against public transport terminal function Bandar Raya Payung Sekaki Pekanbaru 2016 has not been carried out with a maximum. It is visible from the supervision of the relevant parties had done but still a many of bus drivers who raise and lower the passengers is not in the terminal. As for the factors that influence the surveillance was human resources, leadership and community participation.Keyword: Supervision, terminal function